The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.1111/j.1524-4725.2009.01259.x
|View full text |Cite
|
Sign up to set email alerts
|

Cryolipolysis for Noninvasive Fat Cell Destruction

Abstract: Cryolipolysis is worthy of further study because it has been shown to significantly decrease subcutaneous fat and change body contour without causing damage to the overlying skin and surrounding structures or deleterious changes in blood lipids.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
128
0
4

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 158 publications
(138 citation statements)
references
References 36 publications
5
128
0
4
Order By: Relevance
“…Findings This nonrandomized interventional cohort study showed that bilateral submental cryolipolysis treatment of 14 participants resulted in a statistically significant reduction in fat thickness (3.77 mm) and skin surface area (1.29 cm 2 ) and yielded high participant satisfaction (93%). Side effects of the procedure were typically mild and included numbness and tingling, which resolved without intervention.…”
Section: Key Pointsmentioning
confidence: 89%
“…Findings This nonrandomized interventional cohort study showed that bilateral submental cryolipolysis treatment of 14 participants resulted in a statistically significant reduction in fat thickness (3.77 mm) and skin surface area (1.29 cm 2 ) and yielded high participant satisfaction (93%). Side effects of the procedure were typically mild and included numbness and tingling, which resolved without intervention.…”
Section: Key Pointsmentioning
confidence: 89%
“…Clinical studies have been performed to characterize any potential effects on the blood lipid profile, and they have documented that cryolipolysis appears to have no significant impact. In the initial preclinical animal studies, no significant changes in the blood lipid or liver profile were observed following multiple cryolipolysis treatments of large body surface areas [14]. Human clinical studies have also shown no significant changes in lipid profiles or liver function tests following cryolipolysis.…”
Section: Complications: How To Avoid Them and How To Treat Themmentioning
confidence: 99%
“…Cryolipolysis is a new method of non-invasive fat layer reduction, which has been shown to significantly reduce fat layer thickness without damage to the skin or other surrounding tissues [1,2]. Adipocytes suffer a fatal apoptotic injury when exposed to cold, as demonstrated by studies on cultured samples [3].…”
Section: Introductionmentioning
confidence: 99%